Noninvasive prenatal testing in the general obstetric population: clinical performance and counseling considerations in over 85000 cases - P. A. Taneja; H. L. Snyder; E. de Feo; K. M. Kruglyak (Publishing House TRILIST, 2017)
The article contains the results of the research, which set two main goals. The first is the determination of the actual indicators of the effectiveness of noninvasive prenatal studies and the development of counseling tools about the predictability of a positive outcome, taking into account certain clinical indicators and the a priori age risk of the mother. The second is the assessment of changes in the clinical and demographic population after the introduction of testing. Objective: The primary goal of this study was to provide clinically relevant information for appropriate patient counseling. Method: Demographics and test metrics were reviewed for 86 658 clinical cases. Outcome information was requested for samples reported as aneuploidy detected or suspected for chromosomes 21, 18, or 13; voluntary outcome reporting was encouraged for all discordant outcomes. Results: Of 86 658 cases, 85 298 (98.4%) met inclusion criteria for result reporting. Of the 1360 (1.6%) cancellations, only 101 (0.1%) were for technical reasons. Average time to result was 3.3 business days. Aneuploidy was detected or suspected in 2142 (2.5%) samples. For aneuploidy detected cases with known clinical outcomes, the overall positive predictive value was 83.5% (608/728); observed positive predictive values for trisomies 21, 18, and 13 ranged from 50.0 to 92.8%. As individual positive predictive values are determined by a patient's prior risk, we developed a chart for counseling patients on positive predictive value based on maternal age. Conclusion: This large-scale report reinforces that noninvasive prenatal testing is a highly accurate screen for fetal aneuploidy in the general obstetric population. Test improvements have facilitated a reduction in failure rates, time to result, and borderline results/unclassifiable results. We have developed a positive predictive value counseling tool to ensure appropriate patient education, counseling, and clinical utilization. Funding sources: This study was funded by Illumina. Conflicts of interest: Authors of article are employees of and hold equity in Illumina.